Oxygen depletion in coastal seas and the effective spawning stock biomass of an exploited fish species. Issue 1 (January 2016) - Hinrichsen, H.-H.; von Dewitz, B.; Dierking, J.; Haslob, H.; Makarchouk, A.; Petereit, C.; Voss, R.
Abstract : Environmental conditions may have previously underappreciated effects on the reproductive processes of commercially exploited fish populations, for example eastern Baltic cod, that are living at the physiological limits of their distribution. In the Baltic Sea, salinity affects neutral egg buoyancy, which is positively correlated with egg survival, as only water layers away from the oxygen consumption-dominated sea bottom contain sufficient oxygen. Egg buoyancy is positively correlated to female spawner age/size. From observations in the Baltic Sea, a field-based relationship between egg diameter and buoyancy (floating depth) could be established. Hence, based on the age structure of the spawning stock, we quantify the number of effective spawners, which are able to reproduce under ambient hydrographic conditions. For the time period 1993–2010, our results revealed large variations in the horizontal extent of spawning habitat (1000–20 000 km 2 ) and oxygen-dependent egg survival (10–80%). The novel concept of an effective spawning stock biomass takes into account offspring that survive depending on the spawning stock age/size structure, if reproductive success is related to egg buoyancy and the extent of hypoxic areas. Effective spawning stock biomass reflected the role of environmental conditions for Baltic cod recruitment better than the spawning stock biomass alone, highlighting the importance of including environmental information in ecosystem-based management approaches.